What is the best approach for immunocompetent patients with a positive skin and a negative blood test for tuberculosis (TB)?. Issue 2 (February 2018) - Van Vooren, Jim; Berg, Mark
Abstract : EVIDENCE‐BASED ANSWER : Patients with a positive tuberculin skin test (TST) and a negative interferon‐gamma release assay (IGRA) may be approached as if they have a negative skin test alone, because the risk of progression to active disease is the same or lower (SOR: B, prospective cohort studies). Expert opinion guidelines do not provide specific recommendations for managing discordant TST and IGRA results.